Method of sequence start of multi-level belt conveyors based on speed control - ZHANG Yajun; QIAO Tiezhu (Gong-kuang zidonghua, 2017)
In order to increase energy-saving efficiency of belt conveyors, a control method of sequence start along the direction of material transport for multi-level belt conveyors was proposed. On the premise of maximum utilization of material cross section on the belt, firstly, matching model between belt speed and load was built. Then, frequency adjustment between belt speed after the soft start and the matching belt speed was implemented by designing scientific and available acceleration curve. Finally, the sequence start control time of multi-level belt conveyors was calculated. The simulation results show that the method increases energy-saving efficiency to 12%.